Co-simulation of hypertensive left ventricle based on computational fluid dynamics and a closed-loop network model. (April 2022) - Zuo, Xiaowen; Xu, Zhike; Jia, Huaping; Mu, Yang; Zhang, Mingming; Yuan, Manli; Wu, Chengwei
Highlights: This study took the left ventricular flow field of patients with hypertensive myocardial hypertrophy as the research object, used MATLAB simulink to establish a closed-loop network cardiovascular model, provided flow boundary conditions for the computational fluid dynamics (CFD) numerical simulation method, and, finally, completed a co-simulation. Myocardial hypertrophy has a significant influence on the blood flow of the left ventricle. Changes in the blood flow make the left ventricular vortex distribution abnormal during the rapid systole and rapid ejection periods, leading to a series of dangerous factors, including increased energy loss, decreased blood flow velocity, and a low cardiac ejection fraction. Abstract: Objective: Hypertension is one of the most common chronic and cardiovascular diseases, with the largest number of deaths. According to clinical experience, long-term hypertension will cause cardiac hypertrophy and other complications, and heart structure remodeling will significantly change the energy characteristics of the heart chambers, and impair heart function. Research shows that, early hypertension can be diagnosed by the blood flow and energy loss in the left ventricle. Therefore, it is important to choose an appropriate method to simulate and predict the flow domain of this ventricle. Methods: This study took the left ventricular flow field of patients with hypertensive myocardial hypertrophy as the research object, used MATLAB-SIMULINK to establish a closed-loop network cardiovascular model, provided flow boundary conditions for the computational fluid dynamics (CFD) numerical simulation method, and, finally, completed a co-simulation. Results: This article compared the degree of agreement between the energy loss in different phases of the heart cavity and clinical experimental data and summarized the characteristics of the flow field in patients with hypertensive myocardial hypertrophy. The analysis of three simulation groups (control group, non-left ventricular hypertrophy group, and left ventricular hypertrophy [LVH] group) showed that the vortices in the LVH group were irregular and not fully developed, accompanied by significant energy loss. Conclusion: The simulation method used in this study is basically consistent with the clinical data. Myocardial hypertrophy has a significant influence on the blood flow of the left ventricle. Changes in the blood flow make the left ventricular vortex distribution abnormal during the rapid systole and rapid ejection periods, leading to a series of dangerous factors, including increased energy loss and a low cardiac ejection fraction.